New knowledge in dragon tree research - Petr Maděra; Fabio Attorre; Kay Van Damme (Journal of Forest Science)
Dragon trees, arborescent members of the genus Dracaena (Asparagaceae), provide a wide range of ecosystem services and have been ethnobotanically important plants since ancient times. Currently, their relictual distribution is fragmented, populations are isolated and often under threat. We provide a brief overview of scientific studies and the state of knowledge on dragon trees published since 2020, when the last review was published. More than 120 papers dealing with dragon trees have appeared, indicating a significant interest in their research, cultural uses and conservation. The most intensively investigated species are Dracaena cochinchinensis, D. cinnabari, D. draco and D. cambodiana. Almost half of the papers deal with the chemical composition of resin and its bioactivity, in addition to studies on ecology, conservation and genetics. Only a few studies are devoted to taxonomy and ethnobotany.